(3OjhGf CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3hbO hajJ CmSYOc Gddg hCSYOfj, HeG hYOJc ef Yed TYQ CHj JeGe hGdEMJLGL dg Ydi ef QO Ydjg hGdLGgd HebOGQg, hCQLh Cf Cchf bO fdJ QVGc s
(3BNQgG (B:s
(3ef bUjOI jgLh HgG GHf GdCYeTj(B: (3COei GdThb egLJg acja Cf JOej eBbjg Je OjhGf CHj JeGe hgPG BNQg Ydi eG ChQOg GdUhdj s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B56 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B770s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs